2014
DOI: 10.2147/ijn.s54864
|View full text |Cite
|
Sign up to set email alerts
|

In vivo enhancement of anticancer therapy using bare or chemotherapeutic drug-bearing nanodiamond particles

Abstract: Background This study investigated the use of nanodiamond particles (NDs) as a promising material for drug delivery in vivo and in vitro. Methods HepG2 cells (a human hepatic carcinoma cell line) were used to determine the characteristics of a nanodiamond-doxorubicin complex (ND-DOX) when taken up by cells in vitro using laser scanning confocal microscopy and dialysis experiments. We also compared the survival rate and histopathology of tumor-bearing mice after treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 40 publications
2
34
0
3
Order By: Relevance
“…A conclusion can be drawn that ND-(Tf-DOX) complexes could release active DOX and intercalate DNA to inhibit DNA replication and cell growth. Thus, after the ND-(Tf-DOX) complex entered the cell, DOX molecules were detached from the ND and then migrated into the nucleus, and this would lead to a sustained functional drug release, which was similar to the function of ND-DOX /ND-PEG-DOX complex reported previously by us [3,9,33]. So the ND-(Tf-DOX) nanomedicine has double features for targeted tumor cells and a sustained drug release.…”
Section: Cytotoxicity Assaysupporting
confidence: 74%
See 2 more Smart Citations
“…A conclusion can be drawn that ND-(Tf-DOX) complexes could release active DOX and intercalate DNA to inhibit DNA replication and cell growth. Thus, after the ND-(Tf-DOX) complex entered the cell, DOX molecules were detached from the ND and then migrated into the nucleus, and this would lead to a sustained functional drug release, which was similar to the function of ND-DOX /ND-PEG-DOX complex reported previously by us [3,9,33]. So the ND-(Tf-DOX) nanomedicine has double features for targeted tumor cells and a sustained drug release.…”
Section: Cytotoxicity Assaysupporting
confidence: 74%
“…It has been previously reported that DOX had completely entered the nucleus when free DOX treated cells for only 1 h [33]. So the result indicated that ND-(Tf-DOX) nanoparticles have a slow or sustained drug release profile, which is analogous with ND-DOX [33]. We then addressed the question "What is intracellular localization of ND-(Tf-DOX)?"…”
Section: A Lot Of Literatures Have Been Reported That Transferrin-cmentioning
confidence: 89%
See 1 more Smart Citation
“…Some studies indicated that drug molecules can be adsorbed by ND thus forming the complex drug-ND, and with these approaches, water-insoluble drugs may be delivered to cells to effectively exert biological action. The main drugs involved in these studies on drug delivery vehicles, including those for cancer treatment, are doxorubicin hydrochloride (DOX) [22,25], purvalanol A, and 4hydroxytamoxifen [24] as well as insulin therapeutics for diabetes [23].…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…It has been suggested that the molecules of chemotherapeutic drugs bond with the ND surface mainly through electrostatic interactions or hydrogen bonds (HBs) between the drug to be studied and a carboxyl or hydroxyl group of functionalized ND [22][23][24][25]. Theoretical studies on chemical properties of the ND-TAM complex are important for understanding the relation between this complex and interaction with an estrogen receptor.…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%